Meso-Dihydroguaiaretic Acid Ameliorates Acute Respiratory Distress Syndrome through Inhibiting Neutrophilic Inflammation and Scavenging Free Radical - Yen-Tung Lee; Yu-Li Chen; Yi-Hsuan Wu; Ih-Sheng Chen; Hsun-Shuo Chang; Yi-Hsuan Wang; Shih-Hsin Chang; Yi-Hsiu Wu; Ting-I Kao; Huang-Ping Yu; Tsong-Long Hwang (MDPI AG, 2022)
The pathogenesis of acute respiratory distress syndrome (ARDS) is very complex. Patients with ARDS still suffer high mortality rates. Infiltration and activation of neutrophils in lungs are critical pathogenic factors in ARDS. In this study, we demonstrate that meso-dihydroguaiaretic acid (MDGA), a natural lignan, inhibits inflammatory responses in human neutrophils and ameliorates ARDS in mice. MDGA inhibited superoxide anion generation and elastase release in various G-protein coupled receptor agonists-induced human neutrophils. However, MDGA did not alter superoxide anion generation and elastase activity in cell-free systems. These results suggest that the anti-inflammatory effects of MDGA are mediated by regulating cellular signals in human neutrophils. In consistent with this, MDGA suppressed phosphorylation of extracellular signal-regulated kinase and c-Jun N-terminal kinase in activated human neutrophils. Moreover, MDGA inhibited CD11b expression and adhesion in activated human neutrophils. Interestingly, MDGA reduced reactive oxygen species (ROS) generation but not superoxide anion generation in protein kinase C (PKC) activator-induced human neutrophils, suggesting that MDGA may also have ROS scavenging ability. Indeed, MDGA showed strong free radical scavenging activity in cell-free assays. Significantly, MDGA suppressed PKC-induced neutrophil extracellular trap formation. Additionally, treatment of MDGA attenuated neutrophil infiltration and lung damage on lipopolysaccharide-induced ARDS in mice. In conclusion, our results demonstrate that MDGA has anti-neutrophilic inflammatory effects and free-radical scavenging activity. We also suggest that MDGA has potential to serve as a lead for developing new therapeutics to treat ARDS.